Early Failure of Lithium–Sulfur Batteries at Practical Conditions: Crosstalk between Sulfur Cathode and Lithium Anode - Lili Shi; Cassidy S. Anderson; Lubhani Mishra; Hong Qiao; Nathan Canfield; Yaobin Xu; Chengqi Wang; TaeJin Jang; Zhaoxin Yu; Shuo Feng; Phung M Le; Venkat R. Subramanian; et al. (Advanced Science, 2022)
Abstract Lithium–sulfur (Li–S) batteries are one of the most promising next‐generation energy storage technologies due to their high theoretical energy and low cost. However, Li–S cells with practically high energy still suffer from a very limited cycle life with reasons which remain unclear. Here, through cell study under practical conditions, it is proved that an internal short circuit (ISC) is a root cause of early cell failure and is ascribed to the crosstalk between the S cathode and Li anode. The cathode topography affects S reactions through influencing the local resistance and electrolyte distribution, particularly under lean electrolyte conditions. The inhomogeneous reactions of S cathodes are easily mirrored by the Li anodes, resulting in exaggerated localized Li plating/stripping, Li filament formation, and eventually cell ISC. Manipulating cathode topography is proven effective to extend the cell cycle life under practical conditions. The findings of this work shed new light on the electrode design for extending cycle life of high‐energy Li–S cells, which are also applicable for other rechargeable Li or metal batteries.